Improving The Ability To Do Addition And Subtraction With Jarimatika Method In Grade 1 Students Of SDN Wangen - Kristiyaningsih, Kristiyaningsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to improve the ability to perform addition and subtraction of numbers up to two numbers. This research was conducted with two cycles, namely cycle I and II, each cycle consisting of 4 stages, namely planning, implementation, observation, and reflection. Data collection methods include: tests, observations, interviews, and student response questionnaires. The research subjects were first grade students of SDN Wangen, Polanharjo District, consisting of 10 students. The results showed an increase from one cycle to the next. The results showed that the application of jarimatika method was in the good category. The test results showed that the application of jarimatika had a good impact on students' counting skills. This can be seen from the results of student observations on student learning outcomes in cycle I with an average of 60 with 60% classical completeness increased to 85 for the average value with classical completeness reaching 85%, including in the category of very good learning completeness.